Temporal-spatial variation of regulating ecosystem services and analysis of driving factors in Hainan Tropical Rainforest National Park, China - Du, Leshan; Liu, Haiyan; Liu, Haiou; Liu, Wenhui; Li, Ziyuan; Liu, Xiaoyan; Li, Junsheng; Quan, Zhanjun; Zhang, Ying (Frontiers in Earth Science, 2025)
The establishment of national parks is a critical measure for natural ecological protection in China, significantly contributing to biodiversity conservation and regional sustainable development. However, the analysis of temporal-spatial variations in ecosystem services within national parks, along with the factors influencing these variations, remains largely overlooked. This gap limits the effectiveness of ecological protection and refined management in these parks. Using Hainan Tropical Rainforest National Park (HTRNP) as a case study, this study integrates geospatial analysis ArcGIS with the InVEST model to evaluate the regulating ecosystem services (RESs) from 2000 to 2020 at 5-year intervals. The analysis examines the temporal evolution patterns and spatial distribution of RESs, utilizing LightGBM to identify the primary driving factors of these services. The findings reveal the following: (1) Temporally, the RESs exhibit significant fluctuations, with a trend of “initial decline followed by a subsequent rise”. Climate regulation services accounted for the highest proportion at 61.4%, followed by water conservation and soil retention. (2) Spatially, the RESs in the eastern and central regions are slightly higher than those in the western region, demonstrating consistency across different years. The RESs in HTRNP show a strong spatial clustering effect (Moran’s I > 0.5, Z > 2.58), with spatial hotspots (H-H) in the eastern and central regions, and spatial cold spots (L-L) in the western and northern regions. (3) In terms of driving factors, natural factors, including annual precipitation (PRE) and annual potential evapotranspiration (PET) alongside socio-economic factors such as land use and land cover (LULC) and the Human Footprint Index (HFI), make the highest marginal contributions to RESs. Specifically, RESs demonstrate the strongest correlation with LULC, a positive correlation with PRE, and negative correlations with PET and HFI. This study explores the dynamic changes and influencing factors of RESs, providing a scientific guideline for future ecological planning and effective management decisions within HTRNP.